Analysis of the Effect of ICT, Tax and Corruption on Shadow Economy in G20 Countries: Duta Wacana Christian University (Jurnal Ekonomi dan Kebijakan Pembangunan, 2022)
The phenomenon of the shadow economy has become a special concern and is quite interesting from many researchers because of its role that is not visible to the naked eye but whose contribution is quite large in the economy. This paper identifies and analyzes the influence factors of the shadow economy for the G20 countries, which are developing economies and developed countries. The average size of the shadow economy as a proportion of GDP in 2010–2018 in developing countries is around 27 percent, while in developed countries it is around 17 percent. The analytical method used in this study is the fixed effect through panel data in the period 2010-2018. This study uses the MIMIC model as a measure of the shadow economy. The results of this study found that the impact of ICT, Control of Corruption, and taxes significantly affect the shadow economy. The interesting thing and the main implication of this empirical study is that the shadow economy does not only occur in EMDE's countries, but also occurs in advanced economies.